The Effect of Platelet Rich Plasma on Wound Healing in the Repair of Experimental Penile Fractures - Duz, E.; Beger, B.; Saglam, K.; Yildirim, S. (Agricultural Research Communication Centre, 2022)
Background: Penile fractures are caused by the rupture of the tunica albuginea and the underlying layers of corpus cavernosum as a result of the exposure of the erect penis to blunt trauma. Although conservative treatment methods have been recommended in former studies, recent studies favor early surgical options. Platelet-rich plasma (PRP) is a blood product rich in cytokines and several growth factors, obtained from the patient's own blood commonly used to stimulate healing in acute and chronic wound treatments. The efficiency of homologous PRP treatment in rats with penile fractures have been assessed in terms of clinical manifestation and histopathological findings in the present study. Methods: Thirty-five rats were randomly divided into five groups, each containing seven rats as follows: 1. Conservative group: Following the formation of penile fracture, medical interventions were not initiated on fracture area and the wound was left for secondary healing. 2. Bandage group: Following the formation of penile fracture, self-adherent elastic bandage (3 M Coban) was applied to the fracture area for three days. 3. Primary repair group: Following the formation of a penile fracture, the lacerated area was repaired with 7/0 vicryl primary sutures. 4. Primary repair + Homologous Platelet Rich Plasma group: Before the operation, 10 cc of blood was taken from one rat under general anesthesia by intracardiac puncture and PRP material was prepared from this blood. Homologous PRP was topically administered on the wound in the fracture area and then the penile fracture was repaired with 7/0 vicryl as simple separate stitches. 5. Non-operative control group: Surgical procedures were not applied to this group; it was used as the control group. Result: The effect of the PRP treatments on the surgical repair options in the rats with penile fractures was investigated. The present findings revealed that following the repair with conservative treatments, the fracture format persisted and various complications like infection, oedema, excessive fibrosis and hyperemia were encountered. On the other hand, the best healing was achieved in primary repair + PRP group in terms of clinical manifestation and histopathological findings.
Keywords: Penile fracture; Platelet-rich plasma; Rat